Planned vaginal birth or elective repeat caesarean: patient preference restricted cohort with nested randomised trial. - Caroline A Crowther (Public Library of Science (PLoS), 2012)
Background Uncertainty exists about benefits and harms of a planned vaginal birth after caesarean (VBAC) compared with elective repeat caesarean (ERC). We conducted a prospective restricted cohort study consisting of a patient preference cohort study, and a small nested randomised trial to compare benefits and risks of a planned ERC with planned VBAC. Methods and findings 2,345 women with one prior caesarean, eligible for VBAC at term, were recruited from 14 Australian maternity hospitals. Women were assigned by patient preference (n = 2,323) or randomisation (n = 22) to planned VBAC (1,225 patient preference, 12 randomised) or planned ERC (1,098 patient preference, ten randomised). The primary outcome was risk of fetal death or death of liveborn infant before discharge or serious infant outcome. Data were analysed for the 2,345 women (100%) and infants enrolled. The risk of fetal death or liveborn infant death prior to discharge or serious infant outcome was significantly lower for infants born in the planned ERC group compared with infants in the planned VBAC group (0.9% versus 2.4%; relative risk [RR] 0.39; 95% CI 0.19-0.80; number needed to treat to benefit 66; 95% CI 40-200). Fewer women in the planned ERC group compared with women in the planned VBAC had a major haemorrhage (blood loss ≥ 1,500 ml and/or blood transfusion), (0.8% [9/1,108] versus 2.3% [29/1,237]; RR 0.37; 95% CI 0.17-0.80). Conclusions Among women with one prior caesarean, planned ERC compared with planned VBAC was associated with a lower risk of fetal and infant death or serious infant outcome. The risk of major maternal haemorrhage was reduced with no increase in maternal or perinatal complications to time of hospital discharge. Women, clinicians, and policy makers can use this information to develop health advice and make decisions about care for women who have had a previous caesarean. Trial registration Current Controlled Trials ISRCTN53974531